Alcohol-attributable healthcare attendances up to 10 years prior to diagnosis of alcoholic cirrhosis: a population based case-control study - Otete, Harmony E.; Orton, Elizabeth; Fleming, Kate M.; West, Joe (Wiley, 2016)
BACKGROUND & AIMS: Cirrhosis because of alcohol could be avoided if drinking behaviour could be altered earlier in the disease course. Our aim was to quantify the burden of morbidities in patients prior to alcoholic cirrhosis diagnosis, as this may inform the earlier identification of people at high risk for targeted interventions.